Imposition of Land and Building Acquisition Duty on Legally Certain Transaction Agreements: Study of the Indonesian Constitutional Court Decision Number 117/PUU-XXI/2023 - Arofah, Nurwegia Rahmawati; Waluyo, Waluyo; Sasmini, Sasmini (Dinasti Research, 2025)
The title of this research is the “Imposition of Land and Building Acquisition Duty on Legally Certain Transaction Agreements: Study of the Indonesian Constitutional Court Decision Number 117/PUU-XXI/2023”. The object of this research is the Indonesian Constitutional Court Decision Number 117/PUU-XXI/2023. The objective of this research is to discover whether or not the imposition of Land and Building Acquisition Fee on Sale and Purchase Binding Agreement in the Decision of the Constitutional Court of the Republic of Indonesia Number 117/PUU-XXI/2023 provide legal certainty for the community. The method of this research was the normative or doctrinal legal research which employed the statute approach, conceptual approach, and case approach. This research employed primary and secondary legal materials. Results showed that Land and Building Acquisition Tax is a tax imposed on the acquisition of land and/or building rights. Market value reflects the amount of money the seller, as the owner of the land and building, should receive and the buyer, as the party receiving the rights to the land and building being traded. The results of this study are expected to provide information and solutions for parties who study the legal implications and legal certainty for the community regarding the imposition of Land and Building Acquisition Duty on Transaction Agreements in the Decision of the Constitutional Court of the Republic of Indonesia Number 117/PUU-XXI/2023.